2009
DOI: 10.1371/journal.pgen.1000699
|View full text |Cite
|
Sign up to set email alerts
|

Restricting Dosage Compensation Complex Binding to the X Chromosomes by H2A.Z/HTZ-1

Abstract: Dosage compensation ensures similar levels of X-linked gene products in males (XY or XO) and females (XX), despite their different numbers of X chromosomes. In mammals, flies, and worms, dosage compensation is mediated by a specialized machinery that localizes to one or both of the X chromosomes in one sex resulting in a change in gene expression from the affected X chromosome(s). In mammals and flies, dosage compensation is associated with specific histone posttranslational modifications and replacement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 107 publications
3
45
0
Order By: Relevance
“…Intriguingly, a recent study suggests that the DCC may not repress genes by direct binding; rather, the DCC may act at a distance, possibly by bringing dosage-compensated genes to the vicinity of DCC-bound sites (Jans et al 2009). Another study provided evidence that the histone H2A variant H2A.Z might function in dosage compensation through a mechanism that helps restrict the DCC to the X chromosome (Petty et al 2009). Thus, information from these studies on condensin I DC should provide a paradigm that will readily be applicable to our understanding of the general mechanisms of action of condensins.…”
Section: Dosage Compensation In C Elegansmentioning
confidence: 99%
“…Intriguingly, a recent study suggests that the DCC may not repress genes by direct binding; rather, the DCC may act at a distance, possibly by bringing dosage-compensated genes to the vicinity of DCC-bound sites (Jans et al 2009). Another study provided evidence that the histone H2A variant H2A.Z might function in dosage compensation through a mechanism that helps restrict the DCC to the X chromosome (Petty et al 2009). Thus, information from these studies on condensin I DC should provide a paradigm that will readily be applicable to our understanding of the general mechanisms of action of condensins.…”
Section: Dosage Compensation In C Elegansmentioning
confidence: 99%
“…Previous studies reported a decrease in HTZ-1 (histone H2A variant) occupancy (60,77) and decreased levels of H3K4me3 on dosage-compensated X chromosomes (59). Other work has shown an increase in nucleosome occupancy at X-linked gene promoters that is sequence, and not DCC, dependent (16).…”
mentioning
confidence: 96%
“…bet-1(os46) is a nonsense mutation (Shibata et al, 2010). bet-1(gk425), htz-1(tm2469) and mys-1(n4075) are deletions (Ceol and Horvitz, 2004;Whittle et al, 2008;Petty et al, 2009;Shibata et al, 2010). gk425 is a weak allele, because its phenotype is weaker than that of the null allele, os46 (Shibata et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…HTZ-1 facilitates the transcriptional activation of the PHA-4 targets during foregut development (Updike and Mango, 2006). In addition, HTZ-1 restricts the dosage compensation complex that downregulates gene expression by ~50% along the X chromosome, suggesting positive transcriptional roles for HTZ-1 (Petty et al, 2009). A negative role for HTZ-1 in transcriptional regulation has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%